2020
DOI: 10.1177/2056305120905366
|View full text |Cite
|
Sign up to set email alerts
|

Does Better Media Literacy Protect Against the Desire for Tanned Skin and Propensity for Making Appearance Comparisons?

Abstract: Media literacy interventions provide education about the way media influence attitudes to tanned skin and promote risky health-related behaviors (e.g., sun exposure). This study tested whether higher levels of media literacy can protect against the internalization of a tanned ideal and participation in appearance comparisons online. A total of 151 young Australians aged 18 to 29 years (61 males, 90 females) completed a measure of media literacy before being randomly assigned to view photos of models with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Increasing SM literacy can also decrease the internalization of the tanned ideology. SM literacy is the ability of a user to evaluate and critically analyze posts, which aims to promote greater skepticism of appearance-related media [ 41 , 42 ]. The self-persuasion theory is another method that can predict healthy behaviors and enhance skin protection intentions: individuals who share skin protection information predictably use those same practices [ 43 - 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing SM literacy can also decrease the internalization of the tanned ideology. SM literacy is the ability of a user to evaluate and critically analyze posts, which aims to promote greater skepticism of appearance-related media [ 41 , 42 ]. The self-persuasion theory is another method that can predict healthy behaviors and enhance skin protection intentions: individuals who share skin protection information predictably use those same practices [ 43 - 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is also supporting evidence for social media literacy as a modifiable intervention target to improve body image (Paxton et al, 2022). Additionally, the buffering role of media literacy is also supported by experimental research (McLean et al, 2016a;Mingoia et al, 2020;Tamplin et al, 2018). For example, participants who have higher baseline media literacy report lower tanned ideal internalization than those with lower baseline media literacy (Mingoia et al, 2020).…”
Section: The Moderating Role Of Media Literacymentioning
confidence: 88%
“…Additionally, the buffering role of media literacy is also supported by experimental research (McLean et al, 2016a;Mingoia et al, 2020;Tamplin et al, 2018). For example, participants who have higher baseline media literacy report lower tanned ideal internalization than those with lower baseline media literacy (Mingoia et al, 2020). Specific to selfie-viewing, the more female viewers believed that the selfies of other women were digitally modified or altered, the less likely they were to internalize the thin ideal (Vendemia & DeAndrea, 2018).…”
Section: The Moderating Role Of Media Literacymentioning
confidence: 95%
“…The results of the study are consistent with those of Levin-Zamir and Bertschi (2018), who concluded that electronic health literacy positively affects health well-being. Furthermore, media literacy protects against health risks (Mingoia et al, 2020). According to the WHO (2020a), people's ability to identify misinformation and recognize low-quality information help generate healthy behavior and combat the infodemic.…”
Section: Discussionmentioning
confidence: 99%
“…Tully et al (2020) propose that news literacy messages through Twitter can modify misinformation perceptions and mitigate the impact of exposure to misinformation regarding health problems through social media. Media literacy skills help people protect themselves against the misinformation arising from social networking site exposure (Mingoia et al, 2020), and they play a substantial role in how the information shared online is perceived (Vraga & Tully, 2019). Hence, social media users with high news literacy are more distrustful of the quality of information being shared.…”
Section: Social Media Health Literacymentioning
confidence: 99%